A Coastal Retracking System for Satellite Radar Altimeter Waveforms: Application to ERS-2 Around Australia - Deng, X.; Featherstone, Will (American Geophysical Union, 2006)
Satellite radar altimeter-derived sea surface heights (SSH) are in error in coastal regions due, in part, to the complex nature of echoes returned from rapidly varying land and sea surfaces. This paper presents improved altimeter-derived SSH results in Australian coastal regions using the waveform retracking technique, which reprocesses the waveform data through a “coastal retracking system”. The system, based upon a systematic analysis of satellite radar altimeter waveforms around Australia, improves SSH data from several retrackers depending on the waveforms' characteristics. Central to the system is the use of two techniques: the least squares fitting and the threshold retracking algorithms. To overcome the problem of fading noise, the fitting algorithm has been developed to include a weighted iterative scheme. The retrackers include five fitting models and the threshold method with varying threshold levels. A waveform classification procedure has also been developed, which enables the waveforms to be sorted and then retracked by an appropriate retracker. Two cycles of 20-Hz waveform data from ERS-2 have been reprocessed using this system to obtain the improved SSH estimates. Using the AUSGeoid98 gravimetric geoid model as a quasi-independent reference, the system improves SSH estimates from beyond ∼22 km to beyond ∼5 km from the coastline.